2022
DOI: 10.2174/1871520621666210609095602
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Interventions in Breast Cancer Survivors: State of the Art in Targeted Rehabilitation Strategies

Abstract: : Breast cancer is the most common malignant tumor and the most prevalent cause of mortality in women. Advances in early diagnosis and more effective adjuvant therapies have improved the long-term survival of these patients. Pharmacotherapies and intrinsic tumor-related factors may lead to a wide spectrum of treatment-related disabling complications, such as breast cancer-related lymphedema, axillary web syndrome, persistent pain, bone loss, arthralgia, and fatigue. These conditions have a detrimental impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 122 publications
0
17
0
Order By: Relevance
“…Furthermore, several RCTs evaluate different exercises, such as yoga, tai-chi, swimming, walking, and Pilates, which emphasized the benefits of supervised exercise on AIA, that is, pain, stiffness, grip strength, and QOL improvements (35,50). Previous studies had shown that exercise had positive impact and significantly improved a wide range of functional, psychological, and physiological markers in individuals regardless of the type of cancer and stages of treatment (51)(52)(53). Exercise might be associated with small decreases in pro-inflammatory markers (54).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several RCTs evaluate different exercises, such as yoga, tai-chi, swimming, walking, and Pilates, which emphasized the benefits of supervised exercise on AIA, that is, pain, stiffness, grip strength, and QOL improvements (35,50). Previous studies had shown that exercise had positive impact and significantly improved a wide range of functional, psychological, and physiological markers in individuals regardless of the type of cancer and stages of treatment (51)(52)(53). Exercise might be associated with small decreases in pro-inflammatory markers (54).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, therapeutic approaches must not be limited to surgery, antineoplastic medication, radiotherapy and psychological intervention alone, but should include the motivation for supportive activities such as exercise, which has great effect on the quality of life and prognosis ( 35 , 99 101 ). A better knowledge of biomarkers is a prerequisite to assess the effects of complementary therapies and to develop personalized strategies for rehabilitation, e.g., regarding the type and dose of exercise ( 9 ). Therefore, the BEGYN study unites multiple validated assessments, allowing cross-linking analyses between the level of physical activity, cardiopulmonary fitness, body composition, biochemical measurements, an in-depth immune status including quantification of circulating lymphocyte subpopulations, mRNA expression and cytokine profiles and an extensive evaluation of psychological factors.…”
Section: Discussionmentioning
confidence: 99%
“…Although modern breast cancer treatment such as improved diagnostic and staging procedures, advanced systemic therapy, surgery and radiotherapy increases long-term survival and clinical outcome of breast cancer patients, there is still a deficiency of supportive and psychosocial care ( 8 ). Breast cancer survivors are at risk of suffering potentially disabling physical and psychological sequelae, such as lymphedema, axillary web syndrome, chronic pain, osteoporosis and fractures, arthralgia, chronic fatigue syndrome and depression ( 9 ). During and after antineoplastic therapy, rehabilitation and complementary therapies are crucial to improve the quality of life and overall prognosis of breast cancer survivors ( 10 12 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations